Skills for competiveness: demands for modern managers - Pravdiva, Alina (My University, 2014)
To be competitive on the labour market, it is necessary for a modem manager to adapt quickly to management activity, to function on a high professional level, to know how effectively act in economic crisis. An important component of manager’s skills is his/her readiness to start and realize new, original, perspective lines of activity in the development of the organization and to organise the staff to fulfil them by creating necessary conditions to meet both the organization’s and employees’ needs.
Keywords: managers; labour market; competitiveness; менеджери; ринок праці; конкурентоспроможність; менеджеры; рынок труда; конкурентоспособность